Montessori from the start the child at home from birth to age three - Lillard, Paula Polk (Schocken Books, 2003)
What can parents do to help their youngest children in their task of self-formation? How does the Montessori method of hands-on learning and self-discovery relate to newborns, infants, and toddlers? This authoritative and accessible book answers these and many other questions. Its comprehensive exploration of the first three years incorporates the furnishings and tools Dr. Montessori created for the care and comfort of babies. From the design of the baby's bedroom to the child-sized kitchen table, from food preparation to clothing and movement, the authors provide guidance for the establishment of a beautiful and serviceable environment for babies and very young children. They also introduce concepts and tasks, taking into account children's ''sensitive periods'' for learning such skills as toilet training.